A personal adversity model of justifying the costs of entrepreneurial action: The case of oil thieves in the Niger DELTA - Shepherd, Dean A.; Osofero, Moses; Wincent, Joakim (Journal of Business Venturing, 2022)
While entrepreneurship can generate economic and social benefits, it can also be a source of negative outcomes. We need to gain a deeper understanding of how individual entrepreneurs interpret their context and engage in entrepreneurial action that can generate substantial negative outcomes. In this paper we shed light on the entrepreneurial process at the micro-level by exploring how bunkerers—oil thieves—engage in, justify, and persist with entrepreneurial action that, while generating some benefits for the entrepreneurs and the local community, causes substantial destruction to the local environment, community, and the entrepreneurs' health. By inductively generating a personal adversity model of justifying entrepreneurial action that generates substantial negative outcomes (for the local community and environment), we provide new insights into (1) the link between aspects of entrepreneurship under adversity and substantial costs (and some benefits) experienced by local communities already facing adverse conditions, (2) how entrepreneurs' claim varying levels of agency in the same justification of the same action and its negative consequences, and (3) how entrepreneurs entangle the self and others to justify their actions and its costs.